Conservation of wild western honey bees Apis Mellifera in the Polissia natural zone of Ukraine: history, sources of nectar and pollen - Sichenko O.; Kryvyi M.; Horchanok A.; Kuzmenko O.; Tytariova O. (Технологія виробництва і переробки продуктів тваринництва)
Preservation of the diversity of wild honey bees is complicated by insufficient knowledge about their distribution and status in individual territories. The wild population of the western honey bee A. Mellifera, which exists in the territory of Polissia of Ukraine, is an aboriginal subspecies and a natural component of the fauna of these places. The purpose of the research is to assess the current state of this population, which has been preserved thanks to the development of the ancient craft of local residents for extracting honey – «bortnitsvo». Such beekeeping is based on the capture of wild swarms and does not involve selective breeding. Wild honey bees are a valuable genetic resource for biodiversity conservation, as they are an important reservoir of local adaptations that determine their survival in the wild. The results of the physical and chemical analysis of honey obtained from the apiaries of local beekeepers of the Polissia Nature Reserve: diastase – 29.73DN, pH – 4.9, F/G – 1.41, HMF – 6.33mg/kg, proline – 608.87mg/kg, and melissopalynological analysis of pollen in honey, % (Callúna vulgáris – 35, Potentilla erecta – 19, Frangula alnus – 10, Lamium purpureum – 8, Vaccinium myrtillus L – 5, Sisymbrium officinale L – 5, Quercus robur L – 4, etc.) confirmed its botanical origin and value as a source of nutrients for bees. The assessment of the frequency of pollen grains showed the absence of pollen of one species in more than 45%. Only two species are defined as secondary. This is the pollen of the Callúna vulgáris L family (Ericaceae) – 35 % and Potentilla erecta L (Rosaceae) – 19 %. Pollen of such species as Frangula alnus L (Rhamnaceae), Lamium purpureum L (Lamiaceae), Vaccinium myrtillus L (Ericaceae), Sisymbrium officinale L (Brassicaceae), Quercus robur L (Fagaceae), Artemisia vulgáris L (Asteraceae), although they occupy the studied honey together 35 % of the total volume of pollen, however, according to the classification, each of these species is defined as important secondary. Pollen of Potentilla erecta L, Frangula alnus L, Lamium purpureum L, as species with the longest flowering season, remain available almost throughout the honey collection season, and the anemophilic pollen-producing tree of the Fagaceae family Quercus robur L is a common source of pollen for honey bees in Polissia forests.